Hello Bunuel, I gave it a try:

I will note h1 the height of high-rise 1 and h2 the height of high-rise 2. SO:

h1 + h2 = x

and h1 = h2 + 37 =>

Q: h2 + z = ?

h2 + h2 + 37 = x => 2h2 = x-37 =? h2 = (x-37)/2

=> h2 + z = (x-37)/2 + z, CORRECT ANSWER C

Bunuel wrote:

The sum of the heights of two high-rises is x feet. If the first high rise is 37 feet taller than the second, how tall will the second high rise be after they add an antenna with a height of z feet to the top?

A. (x+z)/2 + 37

B. 2x−(37+z)

C. (x−37)/2 + z

D. x/2 - 37 + z

E. (2x−37)/z

Kudos for a correct solution.

The OA will be revealed on Sunday

_________________

THANKS = KUDOS. Kudos if my post helped you!

Napoleon Hill — 'Whatever the mind can conceive and believe, it can achieve.'